Implications of mercury and lead concentrations on breeding physiology and phenology in an Arctic bird. (November 2016) - Provencher, J.F.; Forbes, M.R.; Hennin, H.L.; Love, O.P.; Braune, B.M.; Mallory, M.L.; Gilchrist, H.G.
Abstract: Although physiological traits and phenology are thought to be evolved traits, they often show marked variation within populations, which may be related to extrinsic factors. For example, trace elements such as mercury (Hg) and lead (Pb) alter biochemical processes within wildlife that may affect migration and breeding. While there is a growing understanding of how contaminants may influence wildlife physiology, studies addressing these interactions in free-living species are still limited. We examined how four non-essential trace elements (cadmium, Hg, Pb and selenium) interacted with physiological and breeding measures known to influence breeding in a free-living population of common eider ducks ( Somateria mollissima ). We collected blood from female eiders as they arrived at a breeding colony in northern Canada. Blood was subsequently assessed for baseline corticosterone (CORT), immunoglobulin Y (IgY), and the four trace elements. We used model selection to identify which elements varied most with CORT, IgY, arrival condition, and arrival timing. We then used path analysis to assess how the top two elements from the model selection process (Hg and Pb) varied with metrics known to influence reproduction. We found that arrival date, blood Hg, CORT, and IgY showed significant inter-annual variation. While blood Pb concentrations were low, blood Pb levels significantly increased with later arrival date of the birds, and varied negatively with eider body condition, suggesting that even at low blood concentrations, Pb may be related to lower investment in reproduction in eiders. In contrast, blood Hg concentrations were positively correlated with eider body condition, indicating that fatter birds also had higher Hg burdens. Overall, our results suggest that although blood Hg and Pb concentrations were below no-effect levels, these low level concentrations of known toxic metals show significant relationships with breeding onset and condition in female eider ducks, factors that could influence reproductive success in this species. Graphical abstract: Highlights: Eider ducks in the Canadian Arctic have relatively low levels of blood lead and mercury concentrations. Blood mercury concentrations show significant interannual variation, and vary with corticosterone levels. Blood lead levels show significant variation with both body condition and arrival time on the breeding colonies. Results suggest that while lead levels are low, sublethal effects on reproduction may be occurring. Abstract : Low levels of environmental contaminants, such as mercury and lead, may have direct and indirect sub-lethal effects on reproduction in free-living birds.